Urgensi Penyuluhan Agama Islam - Kusnawan, Aep (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
The Islamic religion counselor is not only giving light or explanation in pronunciation and words, but also as together doing it. A counselor leads the society in apllying about what teached. They leadÂ the society in apllying activities with giving road map and explanation about what have to do, beginning as together and solving the problem together also. This model is planted in daily day, that they with consciousness following clues and invitation ofÂ their leader.